THE IMPACTS OF COVID-19 PANDEMIC IN INDONESIA AND CHINA'S HOTEL INDUSTRY: HOW TO OVERCOME IT? - Valda Shabrina Rahma; Gilang Fadhilia Arvianti (Universitas Terbuka, 2020)
2020 is kind of an alarming year for all countries because of the emergence of an outbreak called the Coronavirus or Covid-19 that originated in Wuhan City, China. This outbreak is a concern for the world because many aspects are affected, such as tourism. This research aims to determine the impacts of the Covid-19 outbreak on the hotel industry in Indonesia and China. It is to analyze the efforts to overcome it. Then, this research was held by applying a descriptive qualitative approach and done by discourse analysis. The data obtained comes from a variety of reference sources that support this research. The findings of the research stated that the hotel industry in Indonesia and China were significantly affected by the Covid-19 outbreak since many hotels were forced to close and not operate to reduce the spread of the virus. Thousands of employees were forced to be laid off due to the losses income of the hotel. Several hotels in Indonesia and China decided to be used as hospitals for Covid-19 victims. In conclusion, the unpredictable outbreak at the beginning of 2020 due to a deadly virus called Covid-19 shook the world because it has affected many aspects, including tourism.